Influence of the Global Economy on Evolution of National Economy Due to the Entrepreneurial Supply Chain Management - Argyngazinov, Aibol; Turmakhanbetova, Shaken; Arzayeva, Maiya; Nurgazina, Assel; Shayakhmetova, Sharafat; Mergembayev, Annet; Zeinullina, Aigul (ExcelingTech, 2020)
Abstract— With the help of comparative and descriptive analysis methods notes and presentations of economics as part of entrepreneurial supply chain management in a number of Russian and Kazakhstani industries were investigated. Parameters of economic development of Kazakhstan, Russia, China and other countries were used to illustrate and support the theoretical background of the investigated issue. According to the information provided by industries within the scope of entrepreneurial supply chain management in Russian and Kazakhstan companies, the strategic goal of building foreign economic relations is the effective participation of the country in foreign trade and integration processes in the interests of sustainable growth of the national economy, the welfare of the population and ensuring non-discriminatory conditions for goods, services and capital. The results and methods of the study can be applied by economist to investigate issues of impact of global economy on national economies in various countries, including as part of entrepreneurial supply chain management of various levels. Results demonstrated that There is positive effect of competence on supply chain strategies as it is verified relationship competency of firm’s quality and efficiency orientation.